2011
DOI: 10.1002/pat.1711
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of amino acid ester substituted polyphosphazene microparticles via electrohydrodynamic atomization

Abstract: This study aims to fabricate biodegradable polyphosphazene microparticles by electrohydrodynamic atomization (EHDA) for applications in drug delivery system. Polyphosphazene microparticles with varied morphologies, such as spherical, doughnut‐shaped, and corrugated, were resulted from electrospraying depending on solvents, molecular weight of polyphosphazene, and concentration of polymeric solution. The solubility of polyphosphazene in different solvents was found to be a significant factor determining the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Microspheres were very irregular and displayed a wrinkled surface. In fact, it has been indicated that particles tend to collapse giving rise to a raisin-like morphology when low solute concentration are employed [53]. A solid PBS shell is expected to be formed as a consequence of the rapid evaporation of the solvent.…”
Section: Optimization Of Operational Conditions For Electrospraying Omentioning
confidence: 99%
“…Microspheres were very irregular and displayed a wrinkled surface. In fact, it has been indicated that particles tend to collapse giving rise to a raisin-like morphology when low solute concentration are employed [53]. A solid PBS shell is expected to be formed as a consequence of the rapid evaporation of the solvent.…”
Section: Optimization Of Operational Conditions For Electrospraying Omentioning
confidence: 99%
“…Polymer chains have more time to diffuse and rearrange in the droplet, generating a more homogeneous surface and dense particle. In addition to volatility, the multiple other properties discussed for SDD as the total molecular diffusivity related to the molecular weight, solvent quality, polymer concentration, etc., determine the final morphology [ 245 ].…”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%
“…This kind of synthetic flexibility endows polyphosphazenes with tunable physical and chemical properties. The tunable physicochemical and biocompatible properties of polyphosphazenes make them promising in different biotechnological applications, such as drug delivery, biosensors, scaffolding materials and controlled release [25][26][27]. Moreover, polyphosphazene-based materials have been reported to be efficient supports in enzyme immobilization practices.…”
Section: Introductionmentioning
confidence: 99%